2013
DOI: 10.1111/jgh.12305
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics, and safety of esomeprazole injection/infusion in healthy Chinese volunteers: A five‐way crossover study

Abstract: Esomeprazole administrated by infusion produces better pharmacokinetic and intragastric pH profiles compared with those by injection. The optimal administration schedule for esomeprazole in Chinese subjects is infusion with 40 mg/12 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…PPIs need time to reach their maximum efficacy because it takes time for the drug to accumulate in newly recruited parietal cells, and to maintain a steady state 22. In a human study, it was reported that the intragastric pH value fell below 4 after 15 hours and became unstable after a single IV injection of 40 mg esomeprazole, compared to twice‐daily administration and 24‐hour infusion groups 23. A recent study reported that esomeprazole inhibited gastric acid secretion in a dose‐dependent manner and the MPT that pH ≥4 was 59% after single administration of 1.6 mg/kg esomeprazole in dogs 8.…”
Section: Discussionmentioning
confidence: 98%
“…PPIs need time to reach their maximum efficacy because it takes time for the drug to accumulate in newly recruited parietal cells, and to maintain a steady state 22. In a human study, it was reported that the intragastric pH value fell below 4 after 15 hours and became unstable after a single IV injection of 40 mg esomeprazole, compared to twice‐daily administration and 24‐hour infusion groups 23. A recent study reported that esomeprazole inhibited gastric acid secretion in a dose‐dependent manner and the MPT that pH ≥4 was 59% after single administration of 1.6 mg/kg esomeprazole in dogs 8.…”
Section: Discussionmentioning
confidence: 98%
“…A washout period of 7 days separated the different dosing regimens. Subjects took standard food within 30 minutes at 4 hours and 9 hours postdose …”
Section: Methodsmentioning
confidence: 99%
“…The above measures ensured accurate measurement of plasma esomeprazole concentrations. Intragastric pH was recorded every 10 seconds from 0 to 24 hours postdose using a calibrated pH microelectrode placed approximately 10 cm below the lower esophageal sphincter . HP infection was diagnosed using the C urea breath test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations